Nitrate removal in woodchip-based bioreactors and greenhouse gas formation tradeoffs between under- and over-treatment - Lin, Jing-An; Volkenborn, Nils (Frontiers in Environmental Science, 2025)
Woodchip-based media are increasingly used to remove excess nitrate from groundwater but data on nitrogen removal rates and greenhouse gas formation for different woodchip types, nitrogen loading and temperatures is limited. Here, we present data from a 1-year long column experiment in which the nitrogen removal performance of 4 different aged woodchip media was assessed for a range of nitrogen loading rates at different temperatures. Nitrate removal and greenhouse gas formation (CH4, N2O) were measured under nitrate-replete (excess nitrate in effluent), nitrate-limited (complete nitrate removal) and nitrate-deplete conditions (no nitrate in influent). At 14°C, nitrate removal rates were highest in oak (4.3 g N m−3 day−1) followed by maple/cherry (3.2 g N m−3 day−1), oak/pine (2.2 g N m−3 day−1) and pine (0.4 g N m−3 day−1). At 20°C, nitrate removal rates increased by a factor of 2.6 times in oak, oak/pine and maple/cherry and by a factor of 6 in pine. CH4 and N2O typically did not co-occur in effluent. Maximal effluent CH4 concentrations were observed under nitrate-deplete conditions and CH4 formation rates increased with temperature. In contrast, concentrations of N2O, a denitrification intermediate, were only significantly elevated in partially denitrified effluent under nitrate-replete conditions. The data provided here can help to make more informed decisions on the optimal design of woodchip-based nitrate removing bioreactors to maximize nitrate removal and minimize greenhouse gases formation associated with unavoidable under- and over-treatment of nitrate.